Respuesta :

Answer:

[tex]d = \frac{4 - 3c}{c + 1} [/tex]

Step-by-step explanation:

To make d the subject of formula, we need to rearrange the equation such that we arrive at d= _____.

[tex]c = \frac{4 - d}{d + 3} [/tex]

Remove the fraction by multiplying (d +3) on both sides:

[tex]c(d + 3) = 4 - d[/tex]

Expand:

[tex]cd + 3c = 4 - d[/tex]

Bring all the d terms to one side and move the others to the other side of the equation:

[tex]cd + d = 4 - 3c[/tex]

Factorise d out:

[tex]d(c + 1) = 4 - 3c[/tex]

Divide by (c +1) on both sides:

[tex]d = \frac{4 - 3c}{c + 1} [/tex]

ACCESS MORE